An Imperative to Adjust? Skill Formation in England and Germany - Wentzel, Joachim; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2011)
This book deals with education systems and the change observed within them alongside changes in the wider political economy. The research is conducted by way of a comparative case study of England and Germany. Extending the VoC approach, not only vocational education and training but also school education and higher education are analysed. The point of departure is the puzzling fact that the current reforms of the education systems of both countries are departing from the paths predicted by the VoC approach. The thesis thus argues against institutional path-dependency in the two countries, and in favour of an ideational approach based on discursive institutionalism. This book is essential reading for researchers in the social sciences, comparative political sciences and educational sciences.
Keywords: Social sciences; Political science; Social Sciences; Political Science; Education (general).